2017
DOI: 10.1007/s10126-017-9786-0
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics Reveals Genetic Divergence and Adaptive Differentiation of Chinese Sea Bass (Lateolabrax maculatus)

Abstract: The marine species usually show high dispersal capabilities accompanied by high levels of gene flow. On the other hand, many physical barriers distribute along the continental marginal seas and may prevent dispersals and increase population divergence. These complexities along the continental margin generate serious challenges to population genetic studies of marine species. Chinese sea bass Lateolabrax maculatus distributes broad latitudinal gradient spanning from the tropical to the mid-temperate zones in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The two highly divergent clusters were detected in the Negro River (4-NR-RB) and in the Merin Lagoon (9-ML-QC) basins. Latitudinal differentiation associated with water temperature has also been reported in the Chinese Sea Bass (Lateolabrax maculatus (Cuvier, 1828)) by RAD-seq analysis on populations of the continental marginal seas along the Chinese coast [21]. Furthermore, a parallel pattern of genomic divergence along a latitudinal gradient was found in sunflower (Helianthus genus) studies [80].…”
Section: Genomic Pattern Of Differentiationmentioning
confidence: 65%
See 1 more Smart Citation
“…The two highly divergent clusters were detected in the Negro River (4-NR-RB) and in the Merin Lagoon (9-ML-QC) basins. Latitudinal differentiation associated with water temperature has also been reported in the Chinese Sea Bass (Lateolabrax maculatus (Cuvier, 1828)) by RAD-seq analysis on populations of the continental marginal seas along the Chinese coast [21]. Furthermore, a parallel pattern of genomic divergence along a latitudinal gradient was found in sunflower (Helianthus genus) studies [80].…”
Section: Genomic Pattern Of Differentiationmentioning
confidence: 65%
“…In such an evolutionary context, it was hypothesized that genomic footprints of selection might be associated with local adaptation to different environments and could therefore be retrieved using genomic screening across populations [17].Restriction site-associated DNA sequencing (RAD-seq) is a high-throughput technique that enables the simultaneous identification and genotyping of thousands of SNPs (Single Nucleotide Polymorphisms), indels and microsatellite markers in non-model organisms [18][19][20]. Genome-wide SNP population screening allows assessing genetic diversity, demographic and population structure, adaptive variation and the genetic architecture associated with traits of interest [21]. Neutral and adaptive genetic variation accounts for the demographic history and adaptive evolution of populations [22,23].…”
mentioning
confidence: 99%
“…A recent study identified a genome-wide variation of 22,648 single-nucleotide polymorphisms (SNPs) and used these SNPs to infer population structure and local adaptation of the spotted sea bass [9]. Furthermore, 10,297 SNPs from 219 spotted sea bass individuals belonging to 12 populations along the Chinese coast were used for genetic structure analysis in geographically distant populations [10]. In addition, a comprehensive transcriptome analysis identified sequences of genes involved in salinity adaptation and osmoregulation in the liver of the spotted sea bass, providing insights into the molecular mechanisms behind salinity acclimation in euryhaline teleosts [4].…”
Section: Data Descriptionmentioning
confidence: 99%
“…An earlier study using isozyme and RAPD analyses had revealed differences among L. maculatus Chines populations from north to south (Li et al 2005). In addition, preliminary phylogenetic analysis demonstrated that populations of L. maculatus clustered into different clades, and suggested low genetic diversity within populations (Zhao et al 2018). Genetic diversity and population structure were investigated based on a single mitochondrial gene (COI) in five geographical populations (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%